Sandwich panel of oriented particles with unconventional and waste materials - Barbirato, Guilherme Henrique Ament (2022)
The development of materials using forest biomass by-products makes it possible to replace conventional materials, adds value to the raw material, and contributes to the sector\'s circular economy. A sustainable alternative for these residues would be to transform them into panels of reconstituted forest biomass. In this scope, the present research aimed to optimize the content of castor oil polyurethane resin (PU-Castor) for OSB (Oriented Strand Board) panels made of reforestation wood waste and bamboo and to study the mechanical performance of OSB sandwich panels with flat faces and cores. trapezoidal with application bias as a structural component. The study was designed in 3 stages, namely: 1- optimization of the content of castor oil polyurethane resin for flat OSB panels made of reforestation wood waste and bamboo; 2- development and performance evaluation of OSB sandwich panel with trapezoidal core and flat faces; 3- Analysis of critical regions and faults of OSB sandwich panel specimens. The results obtained in the first stage indicated that the bamboo OSB panels with 8% resin content reached the minimum requirements recommended by the European standard EN 300:2006, for type 1 OSB panels (general use in a dry environment). Panels with a content of 10% met the minimum requirements for type 3 (structural purposes in a humid environment) and panels with a content of 12 and 15% met the normative requirements for OSB panels of type 4 (special structural purposes in a humid environment). On the other hand, for the OSB panels made of reforestation wood waste, only the panels with contents of 10 and 12% reached the minimum normative recommendations for OSB type 2 panels (structural purposes in a dry environment). In the second stage, the OSB sandwich panel presented greater rigidity of the set and lower specific weight and, consequently, a mechanical performance that enables its application as a structural component. In accordance with the recommendations presented by APA-PS 2-10, the OSB sandwich panel can be used in structural, flooring, and ceiling applications. In the third stage, the OSB sandwich panel presented failure regions in the glue line, between the core and the external face, and also, in the external faces with propagation to the core region.